Bahasa Indonesia Bahasa Indonesia - M. Helmi; Asrial Asrial; Bambang Hariyadi (Jurnal Penelitian Pendidikan IPA, 2023)
Learning using the problem-based learning (PBL) enables students to solve problems as well as improve their science knowledge and skills. This study aims to investigate the effect of the use of PBL on critical thinking skills of high school students in biotechnology. Various levels of students’ self-confidence are used as a moderating variable for PBL in producing the effect. A total of 64 students of SMAN 8 Batanghari Jambi were involved in this study. Some 32 students were allocated each to the experimental class which was learning using PBL and the control class which was learning using the expository learning. Data were collected using a pre-validated self-confidence questionnaires and tests of critical thinking skills. The factorial type of quasi-experimental with pretest posttest nonequivalent control group design was used in this study. The collected data were analyzed using a two-way ANOVA test. The results showed that PBL-students had a higher average score of critical thinking skills (85.87) than their counterpart (78.80). The data also showed that the students with better self-confidence also have a higher average score of critical thinking skills (85.32) than those with lower self-confidence (79.34). The results of the two-way ANOVA test showed that there was an effect of the use of PBL and the students' self-confidence on students' critical thinking skills. Even though it is very weak, the interaction between the learning model and the self-confidence was seemingly existed in affecting the students' critical thinking skills. It can be concluded that the appropriate learning model and appropriate self-confidence can affect student learning critical thinking skills